Using Thermodynamics to Predict the Outcomes of Nitrate-Based Oil Reservoir Souring Control Interventions - Dolfing, Jan; Hubert, Casey R. J. (Frontiers in Microbiology, 2017)
Souring is the undesirable production of hydrogen sulphide (H2S) in oil reservoirs by sulphate-reducing bacteria (SRB). Souring is a common problem during secondary oil recovery via water flooding, especially when seawater with its high sulphate concentration is introduced. Nitrate injection into these oil reservoirs can prevent and remediate souring by stimulating nitrate-reducing bacteria (NRB). Two conceptually different mechanisms for NRB-facilitated souring control have been proposed: nitrate-sulphate competition for electron donors (oil-derived organics or H2) and nitrate driven sulphide oxidation. Thermodynamics can facilitate predictions about which nitrate-driven mechanism is most likely to occur in different scenarios. From a thermodynamic perspective the question “Which reaction yields more energy, nitrate driven oxidation of sulphide or nitrate driven oxidation of organic compounds?” can be rephrased as: “What is the equilibrium constant for the acetate driven sulphate reduction to sulphide?” or more precisely: “Is acetate driven sulphate reduction to sulphide exergonic or endergonic?” Our analysis indicates that under conditions encountered in oil fields, sulphate driven oxidation of acetate (or other SRB organic electron donors) is always more favourable than sulphide oxidation to sulphate: the change in Gibbs free energy (ΔGo') for the reaction CH3COO- + SO42- + 2H+ " 2CO2 + HS- + 2H2O is -57.3 kJ, i.e., the equilibrium for this reaction is strongly to the right. That predicts that organotrophic NRB that oxidize acetate would outcompete lithotrophic NRB that oxidize sulphide. However, sulphide oxidation to elemental sulphur is different; ΔGo' for the reaction CH3COO- + 4S0 + 2H2O " 2CO2 + 4HS- + 3H+ is -16.3 kJ under standard conditions at pH 7. Low acetate levels drive this reaction to the left, i.e., make HS- oxidation more favourable than acetate oxidation. Incomplete oxidation of sulphide to S0 is likely to occur when nitrate levels are low, and is favoured by low temperatures; conditions that can be encountered at oil field above-ground facilities where intermediate sulphur compounds like S0 may cause corrosion. These findings have implications for reservoir management strategies and for assessing the success and progress of nitrate-based souring control strategies and the attendant risks of corrosion associated with souring and nitrate injection.